PCR-Based RNA Probes: A Quick and Sensitive Method to Improve Whole Mount Embryo In Situ Hybridizations. (April 2001) - David, Robert; Wedlich, Doris
We have developed a PCR-based technique for the preparation of RNA probes that can be used for whole mount in situ hybridization on embryos. T3 or T7 RNA polymerase promoters were introduced at the 5′ end of gene-specific oligonucleotide primers enabling direct in vitro transcription of purified PCR fragments. We show for various marker genes in Xenopus embryos that this method provides equivalent results as compared to conventional vector-based probe preparation, even when fluorescence detection (FISH) is applied. This method offers a rapid and useful means to prepare gene-specific in situ probes predominantly for expression screens or detection of splice variants that previously required time-consuming cloning steps.